Lombok Cultural Values in Amaq Abir Traditional Theatre - M. Okta Dwi Sastra F.M. Marijo; Wadiyo Wadiyo; Agus Cahyono; Suwardi Endraswara (Universitas Negeri Semarang, 2023)
Traditional theater is part of a culture that is deeply rooted and needs to be preserved. As a manifestation of culture, traditional theatrical arts certainly have characteristics that reflect the traditions, customs, and norms of the local community. Theater is an effective medium for providing information, teaching, educational facilities, and an understanding of the values that are believed by the community. The Amaq Abir Theater, which is a traditional theater for the Sasak tribe, certainly has cultural values that contain the life norms of the supporting community. Therefore, exploring the cultural values contained in the Amaq Abir traditional theater needs to be investigated. The benefits obtained will be in the form of community understanding of the personal value of the Sasak tribe in living their social life, which is built from several Amaq Abir theatrical sign systems, as well as efforts to preserve this traditional theater. This study uses a qualitative-descriptive approach using the semiotic analysis method of Tedeusz Kowzan theater. Data analysis in this study includes data reduction, data presentation, and drawing conclusions. The result of this study is the discovery of cultural values related to the personality of the Sasak people, including Tindih, Maliq, and Merang values, from the results of semiotic analysis based on the Tedeuz Kowzan sign system.